National Judicial Reporting Program, 1992 ([Verlag nicht ermittelbar], 1995)
This data collection tabulates the number of persons convicted of felonies in state courts and describes their sentences. Data were collected from state courts and state prosecutors in 100 counties of the United States. The collection contains sociodemographic information such as age, race, and sex of the felon. Types of offenses committed include homicide, rape, and robbery. Adjudication variables referring to the process between arrest and sentencing are also a part of this dataset. Data can be analyzed at the national level or by the individual counties.